Think Pair Share Model for Cultural Literacy Learning Outcomes in Elementary IPAS: Model Think Pair Share untuk Hasil Pembelajaran Literasi Budaya di Sekolah Dasar IPAS - Benita Batul Maulidiyah; Machful Indrakurniawan (Academia Open, 2025)
General Background Cultural literacy and collaborative learning are essential competencies in elementary social and science education to prepare students for diverse societal contexts. Specific Background In grade IV IPAS classes at SDN Krian II, student achievement on cultural diversity material was low, with an average score of 50% and most learners not meeting the minimum mastery criteria. Knowledge Gap Conventional teacher-centered instruction limited student participation and discussion, indicating the need for a structured cooperative learning approach. Aims This study aimed to improve learning outcomes and cultural literacy through the application of the Think Pair Share model. Results Using Classroom Action Research with two cycles involving 34 students, mastery increased from 6% in the pre-cycle to 47% in Cycle I and 74% in Cycle II, with average scores rising from 50% to 64% and 79%. Novelty The study documents a cycle-based implementation of Think Pair Share in IPAS cultural diversity learning within an authentic elementary classroom context. Implications The findings support the integration of cooperative discussion stages to foster active participation and measurable academic progress in primary education settings. Keywords: Think Pair Share, IPAS Learning, Cultural Literacy, Learning Outcomes, Classroom Action Research Key Findings Highlights: Mastery level rose across two intervention cycles Average scores moved from low to sufficient category Cooperative discussion increased student participation